Toxoplasmosis in dogs and cats in the backland’s mesoregion, northeastern Brazil (Research, Society and Development, 2022)
The clinical and anatomopathological aspects of toxoplasmosis in dogs and cats in the backland’s mesoregion, northeastern Brazil, are described. From 2003 to 2019, the Animal Pathology Laboratory of the Federal University of Campina Grande performed 2,521 necropsies on dogs and 1,332 on cats, of which 17 cases of toxoplasmosis were diagnosed. Dogs of both sexes with ages ranging from 5 months to 9 years were affected. Most of the animals were of mixed breed and semi-domiciled, with concomitant infection by the Canine Distemper Virus. Cats of both sexes ranging in age from 3 months to 3.5 years, mixed breed and semi-domiciled were affected. Most dogs showed neurological signs, while cats’ nonspecific symptoms. Necropsy revealed whitish multifocal areas on the lungs and liver. Histopathology revealed multifocal areas of necrosis associated with tachyzoites of Toxoplasma gondii. In dogs, pathological findings consistent with distemper were identified. The diagnosis of toxoplasmosis was established based on the pathological findings and histomorphological characteristics of the agent, which was confirmed by immunohistochemistry. It is concluded that toxoplasmosis is a systemic disease in dogs and cats, and which in dogs is usually associated with immunosuppression caused by distemper. Immunohistochemistry is recommended to confirm the post-mortem diagnosis.